GENERALIZED CONVERGENCE CHARACTERIZATIONS OF FELLER OPERATOR - Gurcan, Mehmet; Calik, Sinan (Isoss Publ, 2011)
This paper is mainly connected with the generalization of approximation properties of Feller operator. We first introduce the probabilistic properties of the Feller operator and its convergence characterization. We also compute its rates of convergence by means of modulus continuity and moments of random variable X-n. The main theorem is the extension to f((m)) derivatives of function f is an element of C-B((m)) [0,infinity). Finally, we are interested in convergence characterization of Laplace transform via Feller operator.
Keywords: Quantum Groups